Dose-dense neoadjuvant chemotherapy followed by sentinel node mapping and laparoscopic pelvic lymphadenectomy and simple trachelectomy in cervical cancer: update results. (1st November 2019) - Robova, H; Rob, L; Halaska, MJ; Hruda, M; Pichlik, T; Drozenova, J; Skapa, P
Abstract : Introduction/Background: Fertility-sparing surgery is safe only if tumor doesn't exceeded 2 cm in the biggest diameter. When the tumor bigger, surgery must be more radical (abdominal trachelectomy type C2), but pregnancy results aren't promising. Neoadjuvant chemotherapy (NAC) followed by simple trachelectomy could be option. Methodology: Women with squamous cell, adeno and adenosquamous cancers IB2 and IB3 infiltrated less than two third of cervical stroma, were included to prospective study. They received 3 cycles of NAC in ten-days interval (cisplatin 75 mg/m 2, ifosfamide 2g/m 2 (max. 3g) in squamous cancers, cisplatin 75 mg/m 2, doxorubicin 35 mg/m 2 in adeno and adenosquamous cancers). Women underwent sentinel lymph node mapping and laparoscopic pelvic lymphadenectomy. When lymph nodes were negative, simple trachelectomy were performed after one week. Results: Forty women were included in to study (28 IB3 and 12 IB3). Fertility was saved in 29 women (72.5%), five (17.2%) of them recurred (4local and 1 distant) and tree (10.3%) patient died (10.3%). Three women lost fertility after treatment of recurrence; definitively fertility was saved in 26 women. Twenty women want be pregnant until now and 18 (90.0%) became pregnant. Fifteen women delivered 18 babies (1 in 24 weeks, 4 in 28–34 weeks, 3 in 34–36 weeks, 10 in terms). One woman miscarried in first trimester, one in second trimester and one is now pregnant. Conclusion: Oncological results in NAC followed by simple trachelectomy in cervical cancers bigger than 2cm are acceptable (mortality rate 10.3%) and pregnancy results are excellent (pregnancy rate 90.0%), but still it is experimental protocol for full instructed women. Work was supported Charles University research program PROGRES Q 28 (Oncology). Disclosure: Nothing to disclose.